Tofacitinib, a suppressor of NOD2 expression, is a potential treatment for Blau syndrome - Ueki, Yoko; Takimoto-Ito, Riko; Saito, Megumu K.; Tanizaki, Hideaki; Kambe, Naotomo (Frontiers in Immunology, 2023)
Blau syndrome is a rare autosomal dominant autoinflammatory granulomatous disease caused by a mutation in the NOD2 gene. It is characterized by a clinical triad of granulomatous dermatitis, arthritis, and uveitis. Tofacitinib is a pan Janus kinase (JAK) inhibitor used for treatment of Blau syndrome and idiopathic sarcoidosis. Here, we evaluated its effect on inflammatory pathways associated with Blau syndrome. The effect of tofacitinib on downstream pathways regulated by mutant NOD2 was analyzed using luciferase assays with overexpression of NOD2 mutants. The effect of tofacitinib on the upstream pathway for the induction of NOD2 expression and proinflammatory cytokine production was assessed using monocytic cell lines differentiated from Blau syndrome patient-derived induced pluripotent stem cells. Tofacitinib did not suppress the increased spontaneous transcriptional activity of NF-κB by mutant NOD2. In addition, mutant NOD2 was not involved in the transcription of ISRE and GAS, which are activated by type 1 and type 2 interferons (IFN), respectively. On the other hand, IFNγ induced the expression of NOD2, which led to the production of inflammatory cytokines by an autoinflammatory mechanism only in cells with mutant NOD2. Tofacitinib suppressed the induction of NOD2 by IFNγ, thereby inhibiting the production of pro-inflammatory cytokines. Thus, tofacitinib showed anti-inflammatory effects through suppression of NOD2 expression. The JAK inhibitor tofacitinib is a potential therapeutic agent for Blau syndrome because it suppresses the autoinflammation seen in Blau syndrome by inhibiting the expression of NOD2.